Serum resistin increases in gestational diabetes but does not differ among various trimesters - Tahmina Ferdousi; Tania Tofail; Sharmin Jahan; Kishore K. Shil; Hafsa Mahrukh; Muhammad A. Hasanat (Heliyon)
Background and aims: Resistin is inflammatory adipocytokine released from adipose and other tissue. It is thought that it is related to insulin resistance and pathogenesis of gestational diabetes mellitus (GDM). This study was aimed to determine the level of serum resistin in mothers with GDM and normal glucose tolerance (NGT) in all trimesters to see whether it differs among different trimesters as well as between GDM and NGT. Materials and methods: This cross-sectional study included 81 pregnant women with GDM and 86 NGT after challenging three samples of 75 gm oral glucose tolerance test (OGTT) following WHO-2013 criteria. Resistin was measured from serum samples obtained in fasting state during OGTT. Resistin was measured by sandwich ELISA method. Results: Resistin level [13.2(9.85, 16.0) vs. 4.66(3.53, 5.96), median (IQR); p < 0.001] was significantly higher in GDM than NGT group. This was also observed for all the trimesters [1st p < 0.001; 2nd p < 0.001; and 3rd p < 0.001 respectively] between the two groups. However, resistin showed no significant difference (p = NS for all) within each group among the three trimesters. By binary logistic regression, resistin was observed as an independent predictor for GDM (p < 0.001). On the other hand, Receiver operating characteristics (ROC) curve analysis explored resistin (AUC = 0.856; p < 0.001) as a good predictor for GDM. Conclusions: Resistin is statistically and significantly higher in GDM than that of NGT group irrespective of gestational age. It does not differ among three trimesters within any of GDM or NGT mothers. Resistin is a good predictor for GDM.